After the crash : the future of finance - Fuchita, Yasuyuki, 1958-; Herring, Richard; Litan, Robert E., 1950- (UPCC book collections on Project MUSE., 2010)
"Examines the ramifications of the 2007-08 financial crisis on the financial services industry and some of its practices and how these are likely to change in the future"--Provided by publisher.